2017
DOI: 10.3389/fmolb.2017.00059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Theobromine Consumption on Serum Lipoprotein Profiles in Apparently Healthy Humans with Low HDL-Cholesterol Concentrations

Abstract: Scope: Theobromine is a major active compound in cocoa with allegedly beneficial effect on high-density-lipoprotein-cholesterol (HDL-CH). We have investigated the effect of theobromine (TB) consumption on the concentrations of triglyceride (TG) and cholesterol (CH) in various lipoprotein (LP) subclasses.Methods: In a randomized, double-blind, placebo-controlled, cross-over study, 44 apparently healthy women and men (age: 60 ± 6 years, BMI: 29 ± 3 kg/m2) with low baseline HDL-CH concentrations consumed a drink … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…However, the concentrations of HDL-Ch in the FLHS models were noted to first increase and then decrease compared with those the controls. Numerous studies revealed that HDL-Ch is the “favourable cholesterol” in the mammal body and is presented as a scavenger that removes excess cholesterol from the bloodstream 21,22 . Increased fat synthesis leads to an HDL-Ch compensatory increase in transported peripheral excess lipids to the liver during the early stage of FLHS progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentrations of HDL-Ch in the FLHS models were noted to first increase and then decrease compared with those the controls. Numerous studies revealed that HDL-Ch is the “favourable cholesterol” in the mammal body and is presented as a scavenger that removes excess cholesterol from the bloodstream 21,22 . Increased fat synthesis leads to an HDL-Ch compensatory increase in transported peripheral excess lipids to the liver during the early stage of FLHS progression.…”
Section: Discussionmentioning
confidence: 99%
“…Kandungan lemak yang sedikit akibat proses pengolahan (Adeyeye, 2016) dan efek penurunan profil lipid dalam tubuh (Martínez-López et al, 2014;Jacobs et al, 2017;Davinelli et al, 2018) membuat bubuk kokoa dapat dijadikan alternatif pangan penderita hiperlipidemia.…”
Section: Pendahuluanunclassified
“…The results showed that regular consumption of a flavanol-rich soluble cocoa powder in milk improves HDL-c levels in normocholesterolemic and hypercholesterolemic subjects. In contrast, a RCT by Jacobs et al [160] studied the effect of theobromine consumption on TG and cholesterol in various lipoprotein subclass concentrations in 44 apparently healthy women and men (age: 60 ± 6 years, BMI: 29 ± 3 kg/m 2 ) and found that theobromine did not have a significant effect on HDL-c in individuals with a lipoprotein phenotype characterized by low HDL-c and high TG in VLDL [160].…”
Section: Health Potential Of Selected Fruits and Vegetablesmentioning
confidence: 99%
“…and prevent the negative outcome of these diseases. However, while there is a great deal of evidence regarding the beneficial effects on CVD risk, there are also a few studies that have not found the same results [160,167]. The length of the intervention, the source of the cocoa, the bioactive compound studied (theobromine, proanthocyanidins, etc.…”
Section: Health Potential Of Selected Fruits and Vegetablesmentioning
confidence: 99%